One-pot multi-segment condensation strategies for chemical protein synthesis. Issue 4 (19th December 2018) - Zuo, Chong; Zhang, Baochang; Yan, Bingjia; Zheng, Ji-Shen
Abstract : This paper describes recent advances of one-pot multi-segment condensation strategies based on kinetically controlled strategies and/or protecting group-removal strategies in chemical protein synthesis. Abstract : With the growing requirement for otherwise-difficult-to-obtain proteins, it is necessary to develop more efficient chemical protein synthesis methods for rapid access to designed protein samples. In particular, a one-pot multi-segment condensation method, with only one purification step to obtain the final product, is expected to demonstrate unique benefits in chemical protein synthesis, such as the requirement of fewer handling procedures and the higher efficiency in obtaining aimed protein samples. The utilization of the one-pot multi-segment condensation strategy is demonstrated via the synthesis of a series of post-translational modification (PTM) or disease-associated peptides or proteins for basic and advanced scientific research. This review summarizes the recent one-pot multi-segment condensation methods utilized in chemical protein synthesis, in which two aspects of drive-strategies will be mainly included: a kinetically controlled strategy and a protecting group-removal strategy, respectively. On one hand, the activities of peptides in N-terminal thiol amino acids or C-terminal acyl donors can be largely different based on the differences in properties, such as steric hindrance, migration rates, electrophilicity, and introduction of active elements such as selenium, etc . Using the different activities, regio-selective peptide ligation can be performed in a kinetically controlled manner. On the other hand, the protecting group-removal strategy involves various moieties, which can block the activity of functional groups arising from N-terminal thiol amino acids or C-terminal acyl donors, and they can be removed by using additives, and pH- or photo-stimulation conditions with further achievement of chemical protein synthesis by the one-pot strategy.